Gaining control over conjugated polymer morphology to improve the performance of organic electronics. Issue 50 (23rd May 2022) - Kukhta, Nadzeya A.; Luscombe, Christine K.
Abstract : Conjugated polymer (CP) microstructure plays a crucial role in determining the characteristics of a target device. Here, we provide an overview of the key aspects of the CP microstructure-property relationship carried out in our group. Abstract : Conjugated polymers (CPs) are widely used in various domains of organic electronics. However, the performance of organic electronic devices can be variable due to the lack of precise predictive control over the polymer microstructure. While the chemical structure of CPs is important, CP microstructure also plays an important role in determining the charge-transport, optical and mechanical properties suitable for a target device. Understanding the interplay between CP microstructure and the resulting properties, as well as predicting and targeting specific polymer morphologies, would allow current comprehension of organic electronic device performance to be improved and potentially enable more facile device optimization and fabrication. In this Feature Article, we highlight the importance of investigating CP microstructure, discuss previous developments in the field, and provide an overview of the key aspects of the CP microstructure-property relationship, carried out in our group over recent years.